iRepair or I Repair? A Dialectical Process Analysis of Control Enactment in the iPhone Repair Aftermarket - Recker, Jan; Zeiss, Roman; Mueller, Mario (MIS Quarterly, 2024)
We study how Apple and independent repair service providers used different physical, regulatory, and digital instruments to influence each other’s abilities to control the repair aftermarket of the Apple iPhone between 2007 and 2020. We show how the emergence of digital instruments for enacting control, made possible through emerging functionality for tethering, encryption, and temporary binding implemented in the iPhone itself, was shaped by and shaped the actions of Apple and the independent repair service providers, and led to a dominant tension between encrypted authorization and inscription of control through Apple and collective legal action by independent repair service providers. Our analysis provides a more nuanced understanding of control enactment by highlighting the implications of using different mediums for exercising control, and we provide a new way to understand the dialectics involved in enacting control in digital product aftermarkets. Our study provides insights that can inform the regulation of digital product aftermarkets—in particular, the ongoing debate about rights-to-repair legislation.